Juvenile dermatomyositis: nailfold capillaroscopy changes, baseline predictors and disease course over 36 months. - Christen-Zaech, S.; Seshadri, R.; Sundberg, J.; Paller, A.S.; Pachman, L.M. (European Journal of Pediatric Dermatology, 2008)
The Authors underline the importance of nailfold capillaroscopy to establish prognosis and treatment of juvenile dermatomyositis. A loss of capillary end row loop is related with the severity and persistence of skin lesions, but not with muscle involvement. An early and aggressive treatment in presence of severe capillaroscopy changes favors the unicyclic course of the disease and the lack of recurrences.